PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KOMPETENSI PEDAGOGIK GURU DI GUGUS I KECAMATAN SAPURAN KABUPATEN WONOSOBO - Eka Hermawan; Dwi Winarsih; Tita Rosita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of principal leadership and school organizational climate on teachers’ pedagogical competence in elementary schools within Cluster I of Sapuran District, Wonosobo Regency. The background of this study stems from the empirical condition showing that teachers’ pedagogical competence remains inconsistent, as reflected in their ability to plan, implement, and evaluate learning processes. The research employed a quantitative approach with a correlational descriptive method. The sample consisted of 91 teachers selected from a total population of 118 through proportional random sampling. Data were collected using a Likert-scale questionnaire tested for validity and reliability and analyzed using multiple linear regression. The results reveal that both principal leadership and organizational climate significantly influence teachers’ pedagogical competence, with an R² value of 0.550, indicating that 55% of the variation in teachers’ pedagogical competence can be explained by the two independent variables. The principal’s role as a motivator, supervisor, and instructional leader, supported by a positive organizational climate, has proven to enhance teachers’ professionalism and teaching effectiveness. The study concludes that strong instructional leadership and a conducive organizational climate are key factors in improving pedagogical competence in elementary education settings.